Regional convergence analysis for skill-specific employment groups - Daniel Werner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In most of the developed countries the number of low-skilled workers decreased and the number of high-skilled workers increased. However, it is far from clear whether and how this change in the skill composition of the employees affects the evolution of regional employment disparities. Therefore, this paper investigates the hypothesis of convergence for the total employment rate and skill-specific employment rates of West German regional planning units for the time period 1989 to 2008. This paper considers different concepts of convergence. Following the cross-sectional approach to convergence provides no evidence for a catching-up process between regions. The findings from the time series approach to convergence are mixed. The results indicate for stochastic convergence in the case of total and high-skilled employment rates whereas the hypothesis of stochastic convergence is rejected for regional low-skilled and medium-skilled employment rates.
Keywords: C23; J21; R23; 330